A multi‐omics analysis for the prediction of neurocognitive disorders risk among the elderly in Macao. Issue 6 (13th June 2022) - Han, Yan; Quan, Xingping; Chuang, Yaochen; Liang, Qiaoxing; Li, Yang; Yuan, Zhen; Bian, Ying; Wei, Lai; Wang, Ji; Zhao, Yonghua
Abstract: Background: Due to the increasing ageing population, neurocognitive disorders (NCDs) have been a global public health issue, and its prevention and early diagnosis are crucial. Our previous study demonstrated that there is a significant correlation between specific populations and NCDs, but the biological characteristics of the vulnerable group predispose to NCDs are unclear. The purpose of this study is to investigate the predictors for the vulnerable group by a multi‐omics analysis. Methods: Multi‐omics approaches, including metagenomics, metabolomic and proteomic, were used to detect gut microbiota, faecal metabolites and urine exosome of 8 normal controls and 13 vulnerable elders after a rigorous screening of 400 elders in Macao. The multi‐omics data were analysed using R and Bioconductor. The two‐sided Wilcoxon's rank‐sum test, Kruskal–Wallis rank sum test and the linear discriminant analysis effective size were applied to investigate characterized features. Moreover, a 2‐year follow‐up was conducted to evaluate cognitive function change of the elderly. Results: Compared with the control elders, the metagenomics of gut microbiota showed that Ruminococcus gnavus, Lachnospira eligens, Escherichia coli and Desulfovibrio piger were increased significantly in the vulnerable group. Carboxylates, like alpha‐ketoglutaric acid and d ‐saccharic acid, and levels of vitamins had obvious differences in the faecal metabolites. There was a distinct decrease in the expression of eukaryotic translation initiation factor 2 subunit 1 (eIF2α) and amine oxidase A (MAO‐A) according to the proteomic results of the urine exosomes. Moreover, the compound annual growth rate of neurocognitive scores was notably decreased in vulnerable elders. Conclusions: The multi‐omics characteristics of disturbed glyoxylate and dicarboxylate metabolism (bacteria), vitamin digestion and absorption and tricarboxylic acid cycle in vulnerable elders can serve as predictors of NCDs risk among the elderly of Macao. Intervention with them may be effective therapeutic approaches for NCDs, and the underlying mechanisms merit further exploration. Abstract : Multi‐omics characteristics of Macao elderly susceptible to neurocognitive disorders (NCDs) were investigated. Gut microbiota, faecal metabolites and urine exosomes were detected utilizing metagenomics, metabolomic and proteomic. Disturbed glyoxylate and dicarboxylate metabolism (bacteria), vitamin digestion and absorption and tricarboxylic acid cycle can serve as predictors of NCDs risk.